A structured server architecture to stock and share ice core data. From database to a WebGIS application - Locci, F; Dessì, F; Provenzale, A; Vuillermoz, E; Melis, MT; DE AMICIS, MATTIA GIOVANNI MARIA; FRIGERIO, IVAN; STRIGARO, DANIELE; MATTAVELLI, MATTEO (2013)
Nextdata project aim to create a national system for retrieval, storage, access and diffusion of environmental and climate data from mountain and marine areas. For this project a database to collect paleoclimatic data from ice cores and marine cores has been developed. These data derived from drilling projects of non polar glaciers and marine sediments respectively. The activity is based on a catalog system of data and metadata called SHARE GeoNetwork, developed within the EvK2-CNR SHARE project. The database structure to stock data is based on WDB (Water and Weather Database System) architecture, a database developed from Norwegian Meteorological Institute for their operability data-center. This database was chosen because of WDB is released in according to the GNU General Public License and so completly configurable, customizable and shared; furthermore, it is developed in PostgreSQL/PostGIS and it allow to record punctual and grid type hydrometeorological data. In the first step of the project, WDB database has been customized to stock data derived from SHARE high altitude stations. Hereinafter we need to modified WDB source code in order to insert paleoclimatic data. They have a time extension that goes from current period to tens millions years ago. The “data” field of PostgreSQL has a time range from 4713 BC to 294276 AC; consequently every physical and chemical data, analyzed on ice core and marine core samples dated in different age before 4713 AC, cannot be saved into WDB database structure. We have maintained the main model but we have modified a part of the source code inserting new functions to write data into WDB, without time limits. This increase the value of temporal data aspect that is essential for paleoclimatic analysis. So, the new database system called WDBPALEO has been proposed to scientific community.